LPV Control Synthesis for Sensor Senescence in Feedback Control System - Aqeel Madhag (IAES Indonesian Section, 2021)
The senescence of system sensor(s) probably causing degenerate system behavior or systembreakdown. Motivated by that, this work considers the synthesis of a gain scheduling controlfor linear parameter varying (LPV) system via linear matrix inequalities (LMIs) techniquessuch that sensors senescence information incorporated in the design of the controller. That is,the degradation of sensor effectiveness due to senescence is modeled by the variation of sensormeasurements’ noise co-variance. The sensors’ senescence information is incorporated as apart of the scheduling parameters for the LPV controller. The synthesis control matrices via linearmatrix inequalities have been re-structured and re-formalized in a way that they incorporatethe sensors senescence information to synthesize a gain scheduling dynamic output feedback(GS - DOF) control. That is, the existing GS - DOF control design LMIs have been modifiedto include the noise co-variance matrix. The significant achievement is the control design conditionsdescription of GS - DOF control in a way that ensures the desired integrated H2&H1 performances in the presence of sensors senescence, where sensors’ senescence information isincorporated as a part of the scheduling parameters for the LPV controller. In addition, two setsof controllers have been synthesized and studied. The simulation expresses the benefits of theproposed controllers, and closed loop system H1 and H2 performances are also studied. Thesynthesized controller ensures the performance associate with a closed loop, the closed loopsystem stability, and the scheme of control is simple enough for real time implementations.